Birth Defect as Teenage Pregnancy Complication: Narrative Review - Maliki, Fauzan Achmad; Laariya, Tira Alfiani (Ahmad Dahlan Medical Journal, 2024)
Background: Due to its complexity in terms of psycho-social factors as well as maternity and maternal outcomes, teenage pregnancy is still a global issue that receives constant attention. The rate of adolescent fertility (AFR) in Indonesia is 26.64 births per 1000 women who are fertile. Objective: This review article aims to explore the issues of teenage pregnancy, particularly as they relate to congenital abnormalities or birth defect as complications of teenage pregnancy. Method: Database searches were conducted on Pubmed and Google Scholar. Results: We gathered 27 articles with a wide variety of research designs in this review article. Conclusion: Anemia, preeclampsia, and eclampsia are the most frequent maternal complications, while low birth weight (LBW) and preterm labor are the most frequent fetal complications in teenage pregnancy. Gastroschisis is the most prevalent birth defect associated with teen pregnancy, but there is little research on the subject and even fewer comprehensive reviews